2007
DOI: 10.1177/0748233707080908
|View full text |Cite
|
Sign up to set email alerts
|

Testicular toxicity of chlorpyrifos (an organophosphate pesticide) in albino rat

Abstract: Organophosphates are among the most widely used synthetic insect pesticides. The widespread use of organophosphates has stimulated research into the possible existence of effects related with their reproductive toxic activity. Present study was therefore, undertaken to assess the effects of chlorpyrifos on testes, the main organ of male reproduction. Chlorpyrifos at the dose levels of 7.5, 12.5 and 17.5 mg/kg b. wt./day was administered orally to male rats of Wistar strain for 30 days to evaluate the toxic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 26 publications
12
110
0
Order By: Relevance
“…Similarly, Al-Thani et al (2003) observed impaired spermatogenesis coupled with the reduction in the number of females fertilized by male mice treated with the pesticide amitraz. A decline in fertility was also observed by Joshi et al (2007), Yu et al (2009) and Shalaby et al (2010) after the administration of chlorpyrifos, carbendazim or methomyl pesticides to male rats. Maneb-induced infertility was associated to serum testosterone inhibition.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Al-Thani et al (2003) observed impaired spermatogenesis coupled with the reduction in the number of females fertilized by male mice treated with the pesticide amitraz. A decline in fertility was also observed by Joshi et al (2007), Yu et al (2009) and Shalaby et al (2010) after the administration of chlorpyrifos, carbendazim or methomyl pesticides to male rats. Maneb-induced infertility was associated to serum testosterone inhibition.…”
Section: Discussionmentioning
confidence: 90%
“…This could be linked with the testicular and epididymal damage reported in this study. In a similar fi nding, chlorpyrifos was reported to cause severe testicular damage which resulted in reduction in sperm count and thus fertility in male mice (Farag et al, 2010;Joshi et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Chlorpyrifos orally administered to male rats at the dose levels of 7.5, 12.5 and 17.5 mg/kg b. wt. /day for 30 days showed a decrease in serum testosterone concentration (Joshi et al, 2007). Treatment of rats with the insecticide heptachlor suppressed estradiol concentrations in blood and reduced the production of estradiol by ovarian cells of treated rats Rami et al, 1995).…”
Section: Effects Of Organophosphate Insecticides On Endocrine Systemmentioning
confidence: 99%
“…It was observed that, at the end of 4th and 7th weeks there was a statistically significant decrease in sperm counts and sperm motility, increase in abnormal sperm morphology Meltem et al (2007). Joshi et al (2007) investigated the effects of chlorpyrifos on testes. Chlorpyrifos methyl orally administered to male rats at the dose levels of 7.5, 12.5 and 17.5 mg/kg b. wt.…”
Section: Effects Of Organophosphate Insecticides On Male Reproductivementioning
confidence: 99%